Differences between serum and plasma for intact parathyroid hormone measurement in patients with chronic renal failure in routine clinical practice. Issue 9 (26th August 2005) - Twomey, P J; Whitlock, T; Pledger, D R
Abstract : Background: Parathyroid hormone (PTH) is important in the evaluation of patients with calcium metabolism disorders and/or chronic renal disease. Aims: To assess the differences between serum and plasma PTH measurements using the Advia Centaur. Methods: Twenty six paired serum and edetate samples from patients with chronic renal failure were analysed using the Advia Centaur. Results: The EDTA results ranged from 2.3 to 76.1 pmol/litre and the Deming regression equation was: serum = 0.8927 EDTA − 0.447. The percentage difference plot had a mean difference of 13.8% (95% confidence interval, 2.2% to 25.4%; significant). The available time to separation and freezing ranged from 10 to 231 (median, 85) minutes. The correlation coefficient for the percentage difference against the time to separation and the percentage difference against the mean PTH concentration were −0.13 and −0.07, respectively. Conclusions: These results go beyond the previous controlled research conditions by showing that such differences between serum and edentate plasma exist in routine clinical practice. They also show that intra-individual PTH differences as large as 25.0% can exist on the same day between serum and edetate plasma. This may partly explain some of the variability of PTH concentrations found in some patients with chronic renal failure.